2022
DOI: 10.1186/s12906-022-03669-z
|View full text |Cite|
|
Sign up to set email alerts
|

Ginsenoside Rg3 induces apoptosis and inhibits proliferation by down-regulating TIGAR in rats with gastric precancerous lesions

Abstract: Background Ginsenoside Rg3 (GRg3) is one of the main active ingredients in Chinese ginseng extract and has various biological effects, such as immune-enhancing, antitumour, antiangiogenic, immunomodulatory and anti-inflammatory effects. This study aimed to investigate the therapeutic effect of GRg3 on gastric precancerous lesion (GPL) induced by N-methyl-N′-nitro-N-nitrosoguanidine (MNNG) and the potential mechanism of action. Methods The MNNG–ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Verification through experiments found that Erianin, the main active ingredients of Dendrobium officinale, could significantly induce cell apoptosis triggered by MNNNG in a dose-dependent manner through the HRAS-PI3K-AKT pathway ( Wang et al, 2021 ). Lv et al (2022) found that Ginsenoside Rg3 could suppress TIGAR and induce cell apoptosis in MNNG induced gastric precancerous lesion rats. Nariman et al reported that MGN-3/biological bran exerts chemopreventive effects on gastric carcinogenesis in rats by regulating gastric cancer cell apoptosis ( Badr El-Din et al, 2016 ).…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 98%
See 1 more Smart Citation
“…Verification through experiments found that Erianin, the main active ingredients of Dendrobium officinale, could significantly induce cell apoptosis triggered by MNNNG in a dose-dependent manner through the HRAS-PI3K-AKT pathway ( Wang et al, 2021 ). Lv et al (2022) found that Ginsenoside Rg3 could suppress TIGAR and induce cell apoptosis in MNNG induced gastric precancerous lesion rats. Nariman et al reported that MGN-3/biological bran exerts chemopreventive effects on gastric carcinogenesis in rats by regulating gastric cancer cell apoptosis ( Badr El-Din et al, 2016 ).…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 98%
“…Ginsenoside Rg3 is one of the most effective active ingredients in ginseng extract, with a variety of biological effects. Lv et al (2022) reported that Ginsenoside Rg3 could inhibit cell proliferation in MNNG induced gastric precancerous lesion rats. They found that after GRg3 treatment, the expression of TIGAR and the production of NADP, GSH G6PDH decreased, leading to the increase of ROS in the gastric mucosal epithelium, thereby inhibiting abnormal proliferation of gastric mucosal epithelial cells.…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 99%
“…Atrophic gastritis with IM and/or Dys is referred to as precancerous lesions of GC (PLGC) because of its high risk of cancer [ 5 , 6 ]. Blocking or delaying PLGC progression has been proven to be an effective way to prevent GC [ 7 ]. Traditional Chinese medicine states that if the spleen is weak, food is not digested.…”
Section: Introductionmentioning
confidence: 99%
“…
Following publication of the original article [1], the authors identified an error in Figs. 3 and 5.
…”
mentioning
confidence: 99%